PSYCHOLINGUISTICS APPROACHING IN ELT AT SMA SHAILENDRA PALEMBANG - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
English is the target language in which students must be proficient in this global era, it makes even the more difficult. Consequently, to overcome these challenges, teachers need to find an effective way or strategy to use in teaching and learning process. In line with this, psycholinguistics as a study of the psychology of language is realized in language teaching. It helps to study the psychological factors that are possibly involved in languages learning. Psycholinguistics focuses on the application of the actual language and communication. It is necessary to make a decision in applying various methods that allow students to easily understand a language. This study was meant to find out how psycholinguistics approaching which will help the teacher in facing some challenges of English language teaching. This study used a qualitative descriptive analysis. The participants were taken from some teachers. The research data is collected by using interview and observation. The result showed that psycholinguistics approach mainly helps teachers to consider the use of appropriate method to teach in ELT.